Maternal Death From Postpartum Necrotizing Fasciitis Arising in an Episiotomy: A Case Report - Catherine M. Lynch; Donna M. Pinelli; C. Wayne Cruse; William N. Spellacy; John T. Sinnott; Ron G. Shashy (Hindawi Limited, 1997)
Background: Necrotizing fasciitis is a rare condition. We report a fatal case arising from an episiotomy in a previously healthy woman.